IMPLEMENTASI KEPERAWATAN KELUARGA PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) UNTUK PENCEGAHAN DIARE BERULANG PADA ANAK - M. Reza Pahlevi; Huwaina Af ‘idah; Erita Gustina (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Diarrhea in children remains a public health problem that can lead to dehydration, impaired growth and development, and even death. One preventive effort against recurrent diarrhea is the implementation of Clean and Healthy Living Behavior (CHLB) within families. This study aims to describe the implementation of family nursing care in applying CHLB to prevent recurrent diarrhea in children. The research method used a case study approach through stages of family nursing care, including assessment, diagnosis, intervention, implementation, and evaluation. Instruments consisted of observation and interviews with families. The results showed an increase in family knowledge and attitudes after being provided with health education on CHLB, including handwashing with soap, consumption of clean water, maintaining food hygiene, and using sanitary latrines. The implementation of CHLB was effective in reducing the risk of recurrent diarrhea in children by promoting healthier family behaviors. The conclusion of this study is that family nursing care through CHLB implementation is effective in enhancing the prevention of recurrent diarrhea in children. It is recommended that CHLB education be developed as a routine program in family health services to reduce the incidence of recurrent diarrhea in children.